HAMBATAN DALAM MENANAMKAN DISIPLIN SHALAT DHUHA: PERSPEKTIF GURU DAN SISWA - Hanjani, Sofiani; Jumari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This qualitative phenomenological study investigates barriers to instilling discipline in performing the Dhuha prayer from the perspectives of teachers and students at MTsN 15 Jombang. Data were collected through classroom and school observations, in-depth interviews with the fiqh teacher, school principal, curriculum vice-principal, and selected students, as well as document analysis. Data analysis followed stages of reduction, presentation, and conclusion drawing, with source triangulation to enhance validity. Findings reveal three primary categories of barriers: (1) limited intrinsic motivation among students, often linked to varying family religious practices; (2) structural constraints within school routines and time allocation that hinder consistent practice; and (3) the mixed effects of authoritarian strategies—while clear rules and educational sanctions increase short-term compliance, they do not always foster long-term internalization of the habit. The study recommends combining structured, school-based habituation with dialogic and reflective approaches, active parental engagement, and sanction designs that emphasize moral reasoning to convert external compliance into sustained religious practice. These measures aim to strengthen both ritual discipline and character formation